Kitty Hawk / 3. - Smith, Roland, 1951- (I, Q, 2012)
"The president's daughter has been kidnapped by the elusive and lethal Ghost Cell. Quest (Q) and Angela are in hot pursuit with vicious winds and blinding rain thwarting them at every turn"--Provided by publisher.